2021
DOI: 10.1016/j.ajem.2020.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome in a patient previously diagnosed with COVID-19

Abstract: As the COVID-19 pandemic continues to progress, the medical community is rapidly trying to identify complications and patterns of disease to improve patient outcomes. In a recent systematic review, it has been reported that isolated cases of Guillain-Barre Syndrome (GBS) have occurred secondary to COVID-19 infection. GBS is defined as a rare, but potentially fatal, immune mediated disease of peripheral nerves and nerve roots that is usually triggered by infections. The incidence of GBS can therefore increase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…The underlying mechanisms of GBS in COVID-19 are not well understood. It can be likely a postinfectious immune-mediated mechanism or infrequently a para-infectious phenomenon [ 3 ]. Hutchins et al .…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of GBS in COVID-19 are not well understood. It can be likely a postinfectious immune-mediated mechanism or infrequently a para-infectious phenomenon [ 3 ]. Hutchins et al .…”
Section: Discussionmentioning
confidence: 99%
“…After thorough literature review, we found a substantial number of reported cases and case series of Covid-19 infection presented with GBS. Table 1 summarizes demographic, type of relationship with Covid-19, clinical and GBS sub-types, response to specific GBS treatment, and outcome of different GBS cases who presented in concurrent with Covid 19 infection [[ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ],[ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ...…”
Section: Discussionmentioning
confidence: 99%
“…Common neurological symptoms of COVID-19 are headache, dizziness, dysgeusia/ageusia, hyposmia/anosmia, seizure, stroke, and encephalopathy [ 2 ]. There have been reported cases of Guillain-Barré Syndrome (GBS) associated with COVID-19 from different parts of the world [[ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ],[ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ,…”
Section: Introductionmentioning
confidence: 99%
“…Das Konzept zur Pathogenese des Guillain-Barré-Syndroms (GBS) als Prototyp einer postinfektiösen autoimmunen Neuropathie [43] sowie Fallberichte und Fallserien aus besonders von der Pandemie betroffenen Ländern wie Spanien [10], Italien [14], Indien [35] und den USA [8] Neben GBS wurden auch mehrere Fälle eines Miller Fisher-Syndroms (MFS) bei SARS-CoV-2-positiven Patienten be-richtet [4]. Auffallend ist, dass oft keine Anti-Gangliosid-Antikörper im Serum nachweisbar waren.…”
Section: Guillain-barré-syndrom Und Miller Fisher-syndromunclassified